FeMnSi series alloy with remarkable room-temperature shape memory effect for 3D printing and preparation method of FeMnSi series alloy
By designing a FeMnSi alloy composition with low Cr, low Ni, and medium Si, and employing a high-energy-input 3D printing process, the problem of insufficient room-temperature shape memory effect in FeMnSi alloys was solved, achieving significant room-temperature shape memory effect and tensile strength, making it suitable for printing complex structures.
Patent Information
- Application Number
- CN202511736487.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-25
- Publication Date
- 2026-02-03
AI Technical Summary
Existing 3D-printed FeMnSi-based shape memory alloys exhibit poor shape memory effect at room temperature, making it difficult to meet the complex structural requirements of intelligent load-bearing, energy storage, and buffer components.
The FeMnSi alloy composition with low Cr, low Ni, and medium Si content was designed, and combined with selective laser melting 3D printing and laser secondary remelting processes to increase the martensitic phase transformation temperature, increase the stacking fault and dislocation density inside the alloy, optimize the grain size, and promote phase transformation by using high energy input.
It significantly improves the shape memory effect and tensile strength of FeMnSi alloys at room temperature, making them suitable for printing complex structures, adapting to 3D printing processes, and avoiding the risk of cracking.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of metal additive manufacturing technology, and in particular relates to a FeMnSi alloy with significant room temperature shape memory effect for 3D printing and its preparation method. Background Technology
[0002] FeMnSi-based shape memory alloys are generally composed of Fe, Mn, Cr, Ni, and Si elements. They exhibit a significant shape memory effect, the mechanism of which involves a deformation-induced fcc-hcp phase transformation and a subsequent hcp-fcc phase transformation upon heating, ultimately leading to the recovery of the deformed shape from its initial shape. FeMnSi-based shape memory alloys, with a room-temperature bending pre-strain of 5%, can recover 2.5%–4% strain upon heating. Furthermore, their room-temperature and low-temperature strengths are significantly higher than those of NiTi shape memory alloys. Therefore, they hold promise as reusable intelligent load-bearing, energy storage, and buffer components for room-temperature and low-temperature environments in aerospace, robotics, and other fields. FeMnSi-based shape memory alloys exhibit a better shape memory effect when deformed within the temperature range near the martensitic transformation temperature (Ms). The high density of stacking faults and dislocations within the alloy matrix promotes the nucleation of the martensitic phase during deformation, which is also the basis for the superior shape memory effect.
[0003] Since intelligent load-bearing, energy storage, and buffering components typically require complex geometries or porous structures, conventional casting and rolling processes are insufficient for fabricating such components. Therefore, selective laser melting (SLM) 3D printing, offering greater manufacturing freedom, is needed to manufacture FeMnSi-based shape memory alloy intelligent load-bearing, energy storage, and buffering components with complex structures. FeMnSi-based shape memory alloy formulations suitable for traditional rolling and casting processes struggle to achieve good room-temperature shape memory effects in 3D printing. In particular, existing reports on Fe-Mn-Si alloys used for printing, such as Fe-16Mn-6Si-11Cr-6Ni, Fe-17Mn-5Si-10Cr-4Ni, and Fe-21Mn-5Si-9Cr-5Ni, while exhibiting good low-temperature shape memory effects, generally show poor room-temperature shape memory performance.
[0004] Therefore, there is an urgent need to develop a FeMnSi-based printed shape memory alloy with a significant room-temperature shape memory effect. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a FeMnSi alloy with significant room-temperature shape memory effect for 3D printing. This FeMnSi alloy, by designing a composition ratio with low Cr, low Ni, and medium Si content, effectively increases the martensitic transformation point temperature, promotes the phase transformation from the fcc phase to the hcp phase (martensite phase) during room-temperature deformation, and the reverse phase transformation after heating. It exhibits significant shape memory effect and tensile strength at room temperature, while also possessing good adaptability to 3D printing processes, thus solving the problem that existing 3D printed FeMnSi shape memory alloys are difficult to obtain a significant room-temperature shape memory effect.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is: a FeMnSi alloy with significant room temperature shape memory effect for 3D printing, characterized in that the FeMnSi alloy is composed of the following elements by mass percentage: Mn 16%, Cr 7.5%~8.2%, Ni 3.5%~4.2%, Si 5.5%~5.7%, with the balance being Fe.
[0007] The aforementioned FeMnSi alloy with significant room temperature shape memory effect for 3D printing is characterized in that the FeMnSi alloy is composed of the following elements by mass percentage: Mn 16%, Cr 7.5%~8.0%, Ni 3.5%~4.0%, Si 5.5%, with the balance being Fe.
[0008] This invention also discloses a method for preparing the above-mentioned 3D-printed FeMnSi alloy with significant room-temperature shape memory effect, characterized in that the preparation method includes the following steps: Step 1: The powder containing FeMnCrNiSi elements is rotary mixed to obtain a mixed powder; Step 2: Using the mixed powder obtained in Step 1 as raw material, bulk FeMnSi alloy is prepared by selective laser melting 3D printing of metal powder bed.
[0009] The key to achieving room-temperature shape memory effect in FeMnSi alloys lies in increasing the martensitic transformation temperature and the density of defects such as stacking faults and dislocations within the alloy. The relationship between the martensitic transformation temperature (Ms) and the alloy element composition is: Ms(K) = 282 - 6.3%Mn + 37.2%Si - 8.1%Cr - 6.3%Ni. Cr and Ni decrease Ms, while Si increases it. However, low Cr and Ni levels lead to increased stacking fault energy, which in turn reduces the density of stacking faults and dislocations within the alloy, hindering the improvement of room-temperature shape memory effect. Conversely, high Si levels increase brittle phases and reduce plasticity, negatively impacting mechanical properties. 3D printing technology features rapid cooling and cyclic heating during printing, which creates a large number of defects such as dislocations inside the matrix, which is beneficial for shape memory effect. However, the grain size of alloys prepared by 3D printing is much smaller than that of conventional casting (about 1 / 10 of that of conventional casting alloys). The grain size of FeMnSi-based shape memory alloys is too small, which will significantly reduce Ms to a low temperature (about 100K). FeMnSi-based shape memory alloys only have the best shape memory effect when deformed in a temperature range slightly above Ms. Based on the above reasons, this invention combines the characteristics of 3D printing and carefully designs an alloy with low Cr content, low Ni content, and medium Si content: "Mn 16%, Cr 7.5%~8.2%, Ni 3.5%~4.2%, Si 5.5%~5.7%". This allows the printed FeMnSi alloy to improve defect density while reducing the effect of fine grains on the martensitic phase transformation temperature, resulting in a FeMnSi alloy with good shape memory effect and tensile strength at room temperature, while also having good adaptability to 3D printing processes.
[0010] The above-mentioned method for preparing FeMnSi alloys with significant room temperature shape memory effect by 3D printing is characterized in that the laser line energy input of the selective laser melting 3D printing process in step two is above 0.43 J / mm.
[0011] This invention improves the martensitic transformation point temperature by designing the FeMnSi alloy composition, while simultaneously increasing the laser line energy input to intensify internal cyclic heating during printing, promoting strain accumulation, and further increasing the stacking fault and dislocation density within the alloy. Furthermore, this allows the printed FeMnSi alloy to maintain a high stacking fault and dislocation density while increasing Ms (temperature of mass), ultimately resulting in a FeMnSi alloy with significant shape memory effect and tensile strength, and good adaptability to 3D printing processes.
[0012] The above-mentioned method for preparing FeMnSi alloys with significant room temperature shape memory effect by 3D printing is characterized in that, in the process of selective laser melting 3D printing of metal powder bed in step two, laser secondary remelting is performed, and the laser line energy input of the laser secondary remelting is above 0.43J / mm.
[0013] This invention introduces dislocation multiplication or rearrangement through laser secondary remelting, which easily forms stacking faults, especially at material interfaces or phase transformation regions, thereby further increasing the defect density of FeMnSi alloys.
[0014] The above-mentioned method for preparing FeMnSi alloy with significant room temperature shape memory effect by 3D printing is characterized in that a metal wire with a diameter of 1 mm is cut from the FeMnSi alloy block obtained in step two to test the shape memory effect.
[0015] Compared with the prior art, the present invention has the following advantages: 1. This invention addresses the problem of poor room-temperature shape memory effect of existing FeMnSi alloys used for printing. It develops a FeMnSi alloy composition characterized by low Cr content, low Ni content, and medium Si content, combined with a high energy input process. This composition effectively increases the martensitic transformation temperature and reduces the effect of fine grains inside the 3D-printed FeMnSi alloy on the reduction of the martensitic transformation temperature. At the same time, the high energy input significantly improves the removal of defects such as stacking faults and dislocations inside the FeMnSi alloy, which is beneficial to promoting the martensitic transformation during room-temperature deformation and the reverse transformation during subsequent heating, thereby obtaining a higher room-temperature shape memory effect.
[0016] 2. This invention designs the composition of FeMnSi alloys by combining the characteristics of 3D printing process, and obtains FeMnSi alloys with good printing quality, few printing defects, and good shape memory effect and tensile strength at room temperature by controlling the laser line energy input. It is suitable for reusable impact-resistant, load-bearing and functional devices in room temperature environment.
[0017] 3. By slightly increasing the Si content in the FeMnSi alloy, this invention not only increases Ms but also avoids the brittleness of the alloy matrix, eliminating the risk of cracking of the printed parts during 3D printing and laser secondary remelting. At the same time, it maintains a low stacking fault energy, further reducing the adverse effects on the shape memory effect of the FeMnSi alloy.
[0018] 4. This invention introduces a laser secondary remelting process and increases the laser line energy of the laser secondary remelting, thereby increasing the local high-temperature melting and rapid cooling process during the preparation of FeMnSi alloys, which in turn increases stacking fault defects. At the same time, it can adjust the grain size and further reduce the effect of fine grains inside the printed FeMnSi alloy on the reduction of the martensitic phase transformation temperature, resulting in FeMnSi alloys with significant room temperature shape memory effect.
[0019] The technical solution of the present invention will be further described in detail below through embodiments. Detailed Implementation
[0020] Example 1 The FeMnSi alloy of this embodiment is composed of the following elements by mass percentage: Mn 16%, Cr 8%, Ni 4%, Si 5.5%, with the balance being Fe; the preparation method includes the following steps: Step 1: Mix the powder containing FeMnCrNiSi elements by rotary mixing at room temperature to obtain a mixed powder; Step 2: Using the mixed powder obtained in Step 1 as raw material, FeMnSi alloy with dimensions of 100mm×10mm×10mm is prepared by selective laser melting 3D printing and laser secondary remelting process. The parameters of selective laser melting 3D printing and laser secondary remelting process are as follows: laser scanning speed 900mm / s, laser power 390W, and laser line energy input 0.43J / mm.
[0021] Shape memory effect tests were conducted on metal wires with a diameter of 1 mm cut from the FeMnSi alloy prepared in this embodiment. The test method was in accordance with "YS / T 1307.2-2019 Test Method for Memory Performance of Nickel-Titanium Shape Memory Alloys Part 2: Bending Test Method". The test temperature was 298 K (room temperature). The shape memory effect data are shown in Table 1.
[0022] Table 1. Shape memory effect data of FeMnSi alloys
[0023] As shown in Table 1, the FeMnSi alloy prepared in this embodiment has a significant room temperature shape memory effect, indicating that the present invention, by combining the characteristics of the preparation process and using FeMnSi alloy composition with low Cr content, low Ni content and medium Si content, has greatly improved the shape memory effect at room temperature (the index is the shape recovery rate). This will greatly promote the application of FeMnSi shape memory alloy printed parts with complex shapes in a room temperature environment.
[0024] Example 2 The FeMnSi alloy of this embodiment is composed of the following elements by mass percentage: Mn 16%, Cr 7.5%, Ni 3.5%, Si 5.5%, with the balance being Fe; the preparation method includes the following steps: Step 1: Mix the powder containing FeMnCrNiSi elements by rotary mixing at room temperature to obtain a mixed powder; Step 2: Using the mixed powder obtained in Step 1 as raw material, FeMnSi alloy with dimensions of 100mm×10mm×10mm is prepared by selective laser melting 3D printing and laser secondary remelting process. The parameters of selective laser melting 3D printing and laser secondary remelting process are as follows: laser scanning speed 900mm / s, laser power 400W, and laser line energy input 0.44J / mm.
[0025] Shape memory effect tests were conducted on metal wires with a diameter of 1 mm cut from the FeMnSi alloy prepared in this embodiment. The test method was in accordance with "YS / T 1307.2-2019 Test Method for Memory Performance of Nickel-Titanium Shape Memory Alloys Part 2: Bending Test Method". The test temperature was 298 K (room temperature). The shape memory effect data are shown in Table 2.
[0026] Table 2. Shape memory effect data of FeMnSi alloys
[0027] As shown in Table 2, the FeMnSi alloy prepared in this embodiment has a significant room temperature shape memory effect, indicating that the present invention, by combining the characteristics of the preparation process and using FeMnSi alloy composition with low Cr content, low Ni content and medium Si content, has greatly improved the shape memory effect at room temperature (the index is the shape recovery rate). This will greatly promote the application of FeMnSi shape memory alloy printed parts with complex shapes in a room temperature environment.
[0028] Example 3 The FeMnSi alloy of this embodiment is composed of the following elements by mass percentage: Mn 16%, Cr 8.2%, Ni 4.2%, Si 5.5%, with the balance being Fe; the preparation method includes the following steps: Step 1: Mix the powder containing FeMnCrNiSi elements by rotary mixing at room temperature to obtain a mixed powder; Step 2: Using the mixed powder obtained in Step 1 as raw material, FeMnSi alloy with dimensions of 100mm×10mm×10mm is prepared by selective laser melting 3D printing and laser secondary remelting process. The parameters of selective laser melting 3D printing and laser secondary remelting process are as follows: laser scanning speed 900mm / s, laser power 410W, and laser line energy input 0.46J / mm.
[0029] Shape memory effect tests were conducted on metal wires with a diameter of 1 mm cut from the FeMnSi alloy prepared in this embodiment. The test method was based on "YS / T 1307.2-2019 Test Method for Memory Performance of Nickel-Titanium Shape Memory Alloys Part 2: Bending Test Method". The test temperature was 298 K (room temperature). The shape memory effect data are shown in Table 3.
[0030] Table 3. Shape memory effect data of FeMnSi alloys
[0031] As shown in Table 3, the bulk FeMnSi alloy prepared in this embodiment has a significant room temperature shape memory effect. This indicates that the present invention, by combining the characteristics of the preparation process and using FeMnSi alloy composition with low Cr content, low Ni content, and medium Si content, has greatly improved the shape memory effect (indicator: shape recovery rate) at room temperature. This will greatly promote the application of FeMnSi shape memory alloy printed parts with complex shapes in a room temperature environment.
[0032] Example 4 The FeMnSi alloy of this embodiment is composed of the following elements by mass percentage: Mn 16%, Cr 8%, Ni 4%, Si 5.7%, with the balance being Fe; the preparation method includes the following steps: Step 1: Mix the powder containing FeMnCrNiSi elements by rotary mixing at room temperature to obtain a mixed powder; Step 2: Using the mixed powder obtained in Step 1 as raw material, FeMnSi alloy with dimensions of 100mm×10mm×10mm is prepared by selective laser melting 3D printing and laser secondary remelting process. The parameters of selective laser melting 3D printing and laser secondary remelting process are as follows: laser scanning speed 900mm / s, laser power 315W, and laser line energy input 0.45J / mm.
[0033] Shape memory effect tests were conducted by cutting 1 mm diameter metal wires from the FeMnSi alloy prepared in this embodiment. The test method was based on "YS / T 1307.2-2019 Test Method for Memory Performance of Nickel-Titanium Shape Memory Alloys Part 2: Bending Test Method". The test temperature was 298 K (room temperature). The shape memory effect data are shown in Table 4.
[0034] Table 4. Shape memory effect data of FeMnSi alloys
[0035] As shown in Table 4, the FeMnSi alloy prepared in this embodiment has a significant room temperature shape memory effect, indicating that the present invention, by combining the characteristics of the preparation process and using FeMnSi alloy composition with low Cr content, low Ni content and medium Si content, has greatly improved the shape memory effect at room temperature (the index is the shape recovery rate). This will greatly promote the application of FeMnSi shape memory alloy printed parts with complex shapes in a room temperature environment.
[0036] Comparative Example 1 The alloy in this comparative example is composed of the following elements by mass percentage: Mn 16%, Cr 11%, Ni 6%, Si 5.9%, with the balance being Fe; the preparation method includes the following steps: Step 1: Mix the powder containing FeMnCrNiSi elements by rotary mixing at room temperature to obtain a mixed powder; Step 2: Using the mixed powder obtained in Step 1 as raw material, an alloy with dimensions of 100mm×10mm×10mm is prepared by selective laser melting 3D printing and laser secondary remelting process. The parameters of selective laser melting 3D printing and laser secondary remelting process are as follows: laser scanning speed 900mm / s, laser power 380W, and laser line energy input 0.42J / mm.
[0037] Shape memory effect tests were conducted on metal wires with a diameter of 1 mm cut from the FeMnSi alloy prepared in this comparative example. The test method was in accordance with "YS / T 1307.2-2019 Test Method for Memory Properties of Nickel-Titanium Shape Memory Alloys Part 2: Bending Test Method". The test temperature was 298 K (room temperature). The shape memory effect data are shown in Table 5.
[0038] Table 5. Shape memory effect data of alloys
[0039] As shown in Table 5, the alloy prepared in this comparative example deviated from the composition designed in this invention, resulting in a lower room-temperature shape memory effect than that of Examples 1-4. Furthermore, some of the printed parts in this comparative example exhibited cracking. This indicates that only by using the FeMnSi alloy composition characterized by low Cr, low Ni, and medium Si content, as described in this invention, for selective laser melting 3D printing in a metal powder bed can the room-temperature shape memory effect (indicating shape recovery rate) be significantly improved without cracking.
[0040] The above description is merely a preferred embodiment of the present invention and does not constitute any limitation on the present invention. Any simple modifications, alterations, or equivalent structural transformations made to the above embodiments based on the technical essence of the present invention shall still fall within the protection scope of the present invention.
Claims
1. A FeMnSi alloy with significant room-temperature shape memory effect for 3D printing, characterized in that, This FeMnSi alloy is composed of the following elements by mass percentage: Mn 16%, Cr 7.5%~8.2%, Ni 3.5%~4.2%, Si 5.5%~5.7%, with the balance being Fe.
2. The FeMnSi alloy with significant room-temperature shape memory effect for 3D printing according to claim 1, characterized in that, The FeMnSi alloy is composed of the following elements by mass percentage: Mn 16%, Cr 7.5%~8.0%, Ni 3.5%~4.0%, Si 5.5%, with the balance being Fe.
3. A method for preparing a FeMnSi alloy with significant room-temperature shape memory effect by 3D printing as described in claim 1 or 2, characterized in that, The preparation method includes the following steps: Step 1: The powder containing FeMnCrNiSi elements is rotary mixed to obtain a mixed powder; Step 2: Using the mixed powder obtained in Step 1 as raw material, bulk FeMnSi alloy is prepared by selective laser melting 3D printing of metal powder bed.
4. The method for preparing a FeMnSi alloy with significant room-temperature shape memory effect by 3D printing according to claim 3, characterized in that, The laser line energy input for the selective laser melting 3D printing process in step two is above 0.43 J / mm.
5. The method for preparing a FeMnSi alloy with significant room-temperature shape memory effect by 3D printing according to claim 3, characterized in that, In step two, during the selective laser melting 3D printing process of the metal powder bed, a secondary laser remelting is performed, and the laser line energy input for the secondary laser remelting is above 0.43 J / mm.
6. The method for preparing a FeMnSi alloy with significant room-temperature shape memory effect by 3D printing according to claim 3, characterized in that, Shape memory effect tests were conducted by cutting 1 mm diameter metal wires from the FeMnSi alloy described in step two.